2018
DOI: 10.1097/iae.0000000000002109
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Diabetic Retinopathy Progression in Patients With Axial Anisometropia

Abstract: In patients with axial anisometropia, the longer eye had a lower degree of DR progression than the shorter eye. This result showed that elongation of the axial length had a protective effect against the progression of DR without individual confounding factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Long AL may be protective against the development of DR. He et al (2017) conducted an epidemiological investigation and found that type 2 diabetic patients with long AL had a low risk of developing DR. Man et al (2012) stated that long AL is protective for mild, moderate, and severe DR. The mechanism of the protective effect of long AL and myopia on the development and progression of DR remains unknown, and the possible reasons are as follows: (1) Patients with longer AL have reduced retinal blood flow, slower blood velocity, and reduced vessel wall pressure, thus limiting the occurrence and progression of DR ( Lim et al, 2011 ; Kim et al, 2018 ). (2) Disruption of retinal and choroidal blood vessels occurs earlier in patients with high myopia, and the drop in retinal blood perfusion prevents the formation of an abnormal hyperperfusion state that induces DR, thus reducing the risk of developing DR ( Benavente-Pérez et al, 2010 ; Kim et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Long AL may be protective against the development of DR. He et al (2017) conducted an epidemiological investigation and found that type 2 diabetic patients with long AL had a low risk of developing DR. Man et al (2012) stated that long AL is protective for mild, moderate, and severe DR. The mechanism of the protective effect of long AL and myopia on the development and progression of DR remains unknown, and the possible reasons are as follows: (1) Patients with longer AL have reduced retinal blood flow, slower blood velocity, and reduced vessel wall pressure, thus limiting the occurrence and progression of DR ( Lim et al, 2011 ; Kim et al, 2018 ). (2) Disruption of retinal and choroidal blood vessels occurs earlier in patients with high myopia, and the drop in retinal blood perfusion prevents the formation of an abnormal hyperperfusion state that induces DR, thus reducing the risk of developing DR ( Benavente-Pérez et al, 2010 ; Kim et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kim et al performed a retrospective study of DM patients with axial anisometropia with different axis and found that eyes with a longer axial axis had significantly lower DR lesions than those with a shorter axial axis. 25 …”
Section: Discussionmentioning
confidence: 99%
“…[ 57 ] With >1-mm axial length difference between the two eyes, the prevalence of PDR was 61.7% in shorter eyes and 23.5% in longer ones while being significantly lower in eyes with a subfoveal choroidal thickness of <250 μm. [ 66 ] However, subfoveal choroidal thickness is not related to the prevalence and stage of DR when the axial length is >24.5 mm. [ 57 ]…”
Section: Associated Modifying Factorsmentioning
confidence: 99%